Toribio of Astorga and his correspondents. Dogmatic arguments and hierarchical control - Díaz Martínez, Pablo C. (Gerión. Revista de Historia Antigua, 2021)
The omnipresence of Priscillianism in Late Antique Hispania has led to the interpretation of any heretical accusations in the sources from this perspective. However, it is possible that behind the accusations of Manichaeism hid various impostures whose heretical content is thus blurred. This is evident from Toribio de Astorga’s correspondence, although it is also clear that an anti-Priscilian stance was a good opportunity to strengthen one’s own position of power by presenting oneself as a defender of orthodoxy and persecutor of the followers of Prisicillian.